Decolourisation of Reactive Orange 16 by activated carbon and copper oxide catalysts supported on activated carbon - Abdullah, Abdul Halim; Wong, Wan Yuan; Yaziz, Mohammad Ismail (Penerbit Universiti Sains Malaysia, 2010)
Decolourisation of Reactive Orange 16 (RO16) dye by HNO3-modified activated carbons (ACs) and a copper oxide catalyst supported by modified AC (Cu-Ac) were investigated. The percentage of colour removal for AC modified with 12 M HNO3 acid (19%) was found to be lower than that of AC modified using 4 M and 8 M HNO3, which are 23% and 22%, respectively. The Cu-AC, prepared by impregnating the 4 M HNO3-modified AC with copper nitrate solution for a 5 wt% of Cu followed by calcination at 500°C in an N2 atmosphere, shows the highest percentage of removal (63%) compared to the modified and the heat-treated modified AC. Decolourisation of RO16 by the Cu catalyst increases in the presence of H2O2 and UV-light. The decolourisation efficiency of the catalyst under four different conditions was observed to have the following order: Cu-AC/H2O2/UV > Cu-AC/H2O2 > Cu-ACN/UV ≈ Cu-AC.